নারীর আর্থ-সামাজিক উন্নয়ন ও ক্ষমতায়নে সিভিডিপি'র প্রভাব - বেগম, নূরুন্ নাহার
Articles on the role of Comprehensive Village Development Programme (CVDP) in socio-economic development of women in Bangladesh.